La croisade de David Ross McCord / David Ross McCord's Crusade - Wright, Donald (La famille McCord: une vision passionnée / The McCord Family: A Passionate Vision, 1992)
Keywords: McCord (famille); McCord; David Ross

McCORD, DAVID ROSS - Miller, Pamela (Dictionnaire biographique du Canada, 2005)

David Ross McCord - Miller, Pamela (La famille McCord: une vision passionnée / The McCord Family: A Passionate Vision, 1992)
Keywords: McCord (famille); McCord; David Ross

Chroniques visuelles de l'évolution du pays / Visual Records of the Country's Progress - Miller, Pamela (La famille McCord: une vision passionnée / The McCord Family: A Passionate Vision, 1992)
Keywords: McCord (famille); McCord; David Ross

Rononshonni - le Bâtisseur. La collection McCord d'objets ethnographiques - McCaffrey, Moira T. (La famille McCord: une vision passionnée / The McCord Family: A Passionate Vision, 1992)
Keywords: McCord; David Ross; Musée McCord; Musées

The Making and Unmaking of a University Museum: the McCord, 1921-1996 - Young, Brian J. (McGill-Queen's University Press, 2000)
Keywords: McCord (famille); McCord; David Ross; Musée McCord; Musées

Location, Location, Location: David Ross McCord and the Makings of Canadian History - Harvey, Katryn (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2008)
Number: 1
Keywords: McCord (famille); McCord; David Ross; Musée McCord; Musées

David Ross McCord (1844-1930): Imagining a Self, Imagining a Nation - Harvey, Kathryn Nancy (Université McGill, 2006)
This thesis is about the life of David McCord and the contribution he made to Canadian public memory as founder of the McCord Museum of National History. In his McGilI-sponsored museum, founded in 1921, McCord sought to promote a myth of Canadian origins with narration provided by the objects of his personal collection. Integral to this history was the story of the McCord family, their arrival on this continent and their rise to social prominence. In McCord's version of Canadian history, family and personal myth were conflated with that of nation. Viewed through the prism of his collecting and museum work, McCord's life does not easily fit the Carlylean frame adopted by most biographers. In Canadian biographical writing by historians, the 'truth' about a person's life is revealed by following the modernist recipe of painstakingly recreating a detailed chronology of the individual's life. The approach followed here is an important departure from traditional political biography. Entry into McCord's life does not occur at his biological birth date, but at the moment of his own self-fashioned 'birthing', with the opening of the museum realized near the end of his life. In this biographical strategy, McCord's museum acts as a theatre of memory, where fragments of his life story are reassembled to create a narrative of national origins and of personal redemption. In his selection of objects and their display, and in the creation of an archive and the museum itself, McCord left a very elaborate and lasting record of his response to a set of changes associated with industrialization, a process which, in his lifetime, radically transformed the Montreal of his parents' generation. This thesis traces the connection between the creation of a public museum, founded to promote a collective vision of the Canadian past, and the private world of one collector whose collecting practice was defined as much by his own desire to remember and be remembered as it was by the kinds of objects he collected. What makes David McCord's life and collection so compelling is the opportunity it provides from understanding national history from the intimate perspective of one individual.
Keywords: McCord (famille); McCord; David Ross; Musée McCord; Musées

La famille McCord: une vision passionnée / The McCord Family: A Passionate Vision - Miller, Pamela (Musée McCord d'histoire canadienne, 1992)
Keywords: McCord (famille); McCord; David Ross; Musée McCord; Musées

The McCord Family, a Passionate Vision: An Analysis of Artifacts and their Meaning - Argon, George P. (Université Concordia, 1998)
Keywords: McCord (famille); McCord; David Ross; Musée McCord; Musées

Pionniers spirituels, protestants et catholiques / Protestant and Catholic Spiritual Pioneers - Miller, Pamela (La famille McCord: une vision passionnée / The McCord Family: A Passionate Vision, 1992)
Keywords: McCord (famille); McCord; David Ross; Musée McCord; Musées; Protestants